Human Immunodeficiency Virus Infection and Diverse Physical Health Outcomes: An Umbrella Review of Meta-analyses of Observational Studies. (11th August 2019) - Grabovac, Igor; Veronese, Nicola; Stefanac, Sinisa; Haider, Sandra; Jackson, Sarah E; Koyanagi, Ai; Meilinger, Michael; Stubbs, Brendon; Firth, Joseph; Soysal, Pinar; Di Gennaro, Francesco; Demurtas, Jacopo; et al.
Abstract: Background: Our aim was to assess both the credibility and strength of evidence arising from systematic reviews with meta-analyses of observational studies and physical health outcomes associated with human immunodeficiency virus (HIV) but not acquired immunodeficiency syndrome. Methods: We performed an umbrella review of observational studies. Evidence was graded as convincing, highly suggestive, suggestive, weak, or nonsignificant. Results: From 3413 studies returned, 20 were included, covering 55 health outcomes. Median number of participants was 18 743 (range 403–225 000 000). Overall, 45 (81.8%) of the 55 unique outcomes reported nominally significant summary results ( P < .05). Only 5 outcomes (9.0%; higher likelihood of presence of breathlessness, higher chronic obstructive pulmonary disease [COPD] prevalence, maternal sepsis, higher risk of anemia, and higher risk of all fractures among people living with HIV [PLWHIV]) showed suggestive evidence, with P values < 10 –3 ; only 3 (5.5%; higher prevalence of cough in cross-sectional studies, higher incidence of pregnancy-related mortality, and higher incidence of ischemic heart disease among PLWHIV in cohort studies) outcomes showed stronger evidence using a stringent P value (<10 –6 ). None of the unique outcomes presented convincing evidence (Class I), yet 3 outcomes presented highly suggestive evidence, 5 outcomes presented suggestive evidence, and 37 outcomes presented weak evidence. Conclusions: Results show highly suggestive and suggestive evidence for HIV and the presence of a cough, COPD, ischemic heart disease, pregnancy-related mortality, maternal sepsis, and bone fractures. Public health policies should reflect and accommodate these changes, especially in light of the increases in the life expectancy and the incidence of comorbidities in this population. Abstract : This umbrella review captures the complexities and variety of physical outcomes associated with human immunodeficiency virus. It reports on 55 unique outcomes: 3 (higher prevalence of cough and higher incidences of pregnancy-related mortality and ischemic heart disease) had strong evidence.